The cell adhesion molecule Fasciclin2 regulates brush border length and organization in Drosophila renal tubules - Kenneth A. Halberg (Nature Portfolio, 2016)
In Drosophila, Fasciclin 2 (Fas2) has been mainly studied in the nervous system, yet this adhesion protein is more abundant in the adult renal tubule. Here the authors show that Fas2 is essential for brush border maintenance in renal tubules through regulation of microvilli length and organization.